IMPLEMENTASI MODEL PEMBELAJARAN DISCOVERY LEARNING MELALUI PENDEKATAN TARL UNTUK MENINGKATKAN LITERASI SAINS MATERI GETARAN DAN GELOMBANG - Arie Nugroho Ramadhan; Agung Mulyo Setiawan; Sitti Djuwarijah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This research is a classroom action research that focuses on the problem of scientific literacy skills. The purpose of this study is to apply the Discovery Learning learning model with the Teaching at The Right Level approach to improve students' scientific literacy skills. The subjects of the study were 28 students of class VIII C of SMP Negeri 2 Pakis on vibration and wave material. The data collection technique was through learning outcome tests in the form of pretests and posttests, and supported by learning documentation. This research method is one cycle with the stages of planning, action implementation, observation, and reflection. Data analysis was carried out to determine the increase in students' scientific literacy using the n-gain formula. The results of the study showed an increase in students' scientific literacy skills, with a pretest score of 50.35 increasing to 67.67 on the posttest after being given treatment. The results of the n-gain of students' scientific literacy showed a value of 0.34 which is classified as a moderate category. The aspect of scientific literacy with the highest value is the interpretation of data and facts/evidence scientifically, which has an n-gain of 0.5 and is classified as moderate. It is concluded that the application of the Discovery Learning learning model through the TaRL approach is effective in improving students' scientific literacy skills in science subjects.